Pseudomonas syringae AlgU Downregulates Flagellin Gene Expression, Helping Evade Plant Immunity - Bao, Zhongmeng (J Bacteriol, 2020)
Flagella power bacterial movement through liquids and over surfaces to access or avoid certain environmental conditions, ultimately increasing a cell’s probability of survival and reproduction. In some cases, flagella and chemotaxis are key virulence factors enabling pathogens to gain entry and attach to suitable host tissues. However, flagella are not always beneficial; both plant and animal immune systems have evolved receptors to sense the proteins that make up flagellar filaments as signatures of bacterial infection. Microbes poorly adapted to avoid or counteract these immune functions are unlikely to be successful in host environments, and this selective pressure has driven the evolution of diverse and often redundant pathogen compensatory mechanisms. We tested the role of AlgU, the Pseudomonas extracytoplasmic function sigma factor σ(E)/σ(22) ortholog, in regulating flagellar expression in the context of Pseudomonas syringae-plant interactions. We found that AlgU is necessary for downregulating bacterial flagellin expression in planta and that this results in a corresponding reduction in plant immune elicitation. This AlgU-dependent regulation of flagellin gene expression is beneficial to bacterial growth in the course of plant infection, and eliminating the plant’s ability to detect flagellin makes this AlgU-dependent function irrelevant for bacteria growing in the apoplast. Together, these results add support to an emerging model in which P. syringae AlgU functions at a key control point that serves to optimize the expression of bacterial functions during host interactions, including minimizing the expression of immune elicitors and concomitantly upregulating beneficial virulence functions. IMPORTANCE Foliar plant pathogens, like Pseudomonas syringae, adjust their physiology and behavior to facilitate host colonization and disease, but the full extent of these adaptations is not known. Plant immune systems are triggered by bacterial molecules, such as the proteins that make up flagellar filaments. In this study, we found that during plant infection, AlgU, a gene expression regulator that is responsive to external stimuli, downregulates expression of fliC, which encodes the flagellin protein, a strong elicitor of plant immune systems. This change in gene expression and resultant change in behavior correlate with reduced plant immune activation and improved P. syringae plant colonization. The results of this study demonstrate the proximate and ultimate causes of flagellar regulation in a plant-pathogen interaction.